The role of value in extending the lifetime of products: an analysis of perceived value and green consumption values on pro-circular behaviors of repair and reuse (2024)
Promoting circular business models is a clear path to tackling current environmental and social issues. The success of these models depends not only on companies in charge of creating new products, processes, and models that include circular strategies but also on consumers and their choices. Thus, fully understanding consumers and the factors that influence accepting and adopting practices towards circularity is imperative. One of these factors is the relationship that consumers have with the products they purchase and their assessment of these products through the concept of perceived value. This research aimed to explore the relationship between the dimensions of perceived value (i.e., functional, emotional, and social) and pro-circular behaviors of repair and reuse, as well as the role of green consumption values in this relationship. A representative sample of 417 people was surveyed in Medellín (Colombia). Using an Ordinal Logit model, we tested the hypotheses proposed. Findings reveal that functional value is a primary starting point to encourage behaviors aiming to extend the lifetime of products. Moreover, the interaction between sources of value (perceived value and green consumption values) increases the probability of reusing and repairing. Based on these and other relevant results, managerial implications and opportunities for future research are proposed.